2018
DOI: 10.1142/s0218348x18500135
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Self-Similar Space-Filling Sphere Packings

Abstract: Any space-filling packing of spheres can be cut by a plane to obtain a space-filling packing of disks. Here, we deal with space-filling packings generated using inversive geometry leading to exactly selfsimilar fractal packings. First, we prove that cutting along a random hyperplane leads in general to a packing with a fractal dimension of the one of the uncut packing minus one. Second, we find special cuts which can be constructed themselves by inversive geometry. Such special cuts have specific fractal dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The concept of bearings plays an important role on the dynamics of dense packings of particles [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Bearings obtained by construction that completely fill space [23][24][25][26][27][28] can support large pressures while allowing for sliding movement. Moreover, it was shown that the synchronization process necessary to reach a global bearing state can be substantially enhanced by adjusting the inertial contribution of individual rotors [29].…”
mentioning
confidence: 99%
“…The concept of bearings plays an important role on the dynamics of dense packings of particles [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Bearings obtained by construction that completely fill space [23][24][25][26][27][28] can support large pressures while allowing for sliding movement. Moreover, it was shown that the synchronization process necessary to reach a global bearing state can be substantially enhanced by adjusting the inertial contribution of individual rotors [29].…”
mentioning
confidence: 99%